Inspection of Safety and Accuracy of D2 Lymph Node Dissection in Laparoscopy-Assisted Distal Gastrectomy - Kawamura, Hideki; Homma, Shigenori; Yokota, Ryoichi; Yokota, Kentaro; Watarai, Hiroshi; Hagiwara, Masaru; Sato, Masanori; Noguchi, Keita; Ueki, Shinya; Kondo, Yukifumi (World journal of surgery, 2008)
Background There is a consensus on the indication of laparoscopy-assisted distal gastrectomy (LADG) for early gastric cancer that needs D1 + α or D1 + β lymph node dissection. However, many gastrointestinal surgeons consider D2 lymph node dissection in LADG to be difficult, therefore, only a few medical institutions have performed D2 lymph node dissection in LADG. We examined the safety and accuracy of D2 dissection in LADG by comparing with open distal gastrectomy (ODG), as the first step to operate on advanced gastric cancer. Methods The study population comprised 53 and 67 patients who underwent D2 dissection in LADG or ODG, respectively; with the diagnosis of preoperative depth grade SM, between 2004 and 2006. In D2 lymph node dissection, difficult points are dissections of lymph node along the superior mesenteric vein (No. 14v), along the hepatic artery (No. 12a), and along the proximal splenic artery (No. 11p). We performed these lymph nodes dissection in a fixed process, which was achieved through all improvements. Results No significant difference was observed in age, sex, American Society of Anesthesiology (ASA) classification, body mass index (BMI), and operative time between two groups. Bleeding volume was significantly lower in LADG (96.5 ± 126.3 ml) than in ODG (221.9 ± 174.8 ml). There was no significant difference in number of dissected lymph nodes between ODG (44.8 ± 15.6) and LADG (49.2 ± 16.1), with no significant difference in degree of pathological stage. The postoperative complication rate was 16.4% for ODG and 5.7% for LADG, and postoperative hospital stay was significantly shorter for LADG (16.7 ± 5.6 days) than for ODG (21 ± 11.4 days). Conclusions D2 dissection in LADG can be performed without problems with safety and accuracy, if the surgical team is skilled in the procedures of LADG.